Exploring Epistemological Trends in Students' Understanding of Science from the Perspective of Large-Scale Studies. (16th April 2013) - Jakobsson, Anders; Davidsson, Eva; Karlsson, Karl-Göran; Oskarsson, Magnus
Abstract : This paper highlights how results from large-scale studies can be used to understand students' knowledge of science. Several scholars express critique of today's PISA framework, especially with regard to the presentation of the results as national rankings, and suggest alternative and complementary methods. The present study has used PISA data to reveal hidden patterns in the results. The results show a general descending trend in items focusing on the nature of science and how new scientific knowledge is generated. On the other hand, there is an obvious upward trend regarding tasks that measure fact-based elementary or root knowledge. These trends are slightly differentiated at a national level, as the time and magnitude of the decline or increase may vary.